Design for values in architecture: the question of trade-offs - Eloy, S.; Vermaas, P. (Book of abstracts SPT 2019, 2019)
In this paper we consider computer tools for architectural design based on shape grammar design systems and evaluate the advantages and disadvantages of handing over these tools to inhabitants for the design of refurbishments of their apartments. This evaluation is qualitative by considering the values of inhabitants, architects, and cities that are affected by this hand-over. We present shape grammar design systems as a technology that enables design for values in architecture. Such a system also presents a trade-off between the values of inhabitants, architects and cities. We end questioning when to accept trade-offs between the values as tenable.